Pelaksanaan Evaluasi Hasil Belajar Mahasiswa - Nelvia Adi (Jurnal Pendidikan dan Kebudayaan, 2010)
The purpose of this study is to determine the process of the evaluation conducted by the lecturers of UNP, including lattice-making testing, manufacturing problems, the implementation of measurement, assessment and administration of the assessment results. Results revealed that as man as 42 % of lecturers stated always pay attention to making the test grating. There were about 37% of lecturers stated always an often pay attention to the criteria in writing about. In the normal measurement of 75% of lecturers used to pay attention to implementation. In the normal scoring 47% of lecturers stated always and often pay attention to implementation. In conducting the assessment and administration of student learning outcomes, 53% of lecturers claimed always and often pay attention to implementation. Based on these reseaech results may imply that the implementation of the evaluation of learing outcomes by the lectures of UNP normally located in the category well enough, its implementation still needs to be improved again by the lecturers.